2001
DOI: 10.1104/pp.125.1.351
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Maize Amyloplast Stromal 112-kD Protein as a Plastidic Starch Phosphorylase,

Abstract: Amyloplast is the site of starch synthesis in the storage tissue of maize (Zea mays). The amyloplast stroma contains an enriched group of proteins when compared with the whole endosperm. Proteins with molecular masses of 76 and 85 kD have been identified as starch synthase I and starch branching enzyme IIb, respectively. A 112-kD protein was isolated from the stromal fraction by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and subjected to tryptic digestion and amino acid sequence analysis. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…Although exhibiting a vitreous appearance much like T65, pseudonormal seeds were the amyloplasts. A stroma location was also observed for maize endosperm Pho1 (Yu et al, 2001). …”
Section: Pho1 Is Localized In the Stromal Compartment Of Rice Endospementioning
confidence: 73%
See 2 more Smart Citations
“…Although exhibiting a vitreous appearance much like T65, pseudonormal seeds were the amyloplasts. A stroma location was also observed for maize endosperm Pho1 (Yu et al, 2001). …”
Section: Pho1 Is Localized In the Stromal Compartment Of Rice Endospementioning
confidence: 73%
“…Pho1 is localized in amyloplasts, the site of starch synthesis (Yu et al, 2001). Several starch biosynthetic enzymes, such as starch synthase I (SSI), are localized in the amyloplast stroma and are also associated with starch (Fujita et al, 2006).…”
Section: Pho1 Is Localized In the Stromal Compartment Of Rice Endospementioning
confidence: 99%
See 1 more Smart Citation
“…Amylopectin is synthesized by the combined action of several isoforms, including starch synthases (SSs), starch branching synthases (SBEs), and debranching enzymes (DBEs; Nakamura, 2002;Davis et al, 2003;Tetlow, 2006). In addition, starch phosphorylase 1 (Pho1) also has been reported to play a role in starch synthesis, although its precise role remains elusive (Yu et al, 2001;Satoh et al, 2008).…”
mentioning
confidence: 99%
“…Plants possess two types of SP, Pho1 and Pho2, localized to the plastid and cytosol, respectively. A number of studies have found that Pho1 gene expression and activity correlate with other starch biosynthetic enzymes, like SS and SBE, suggesting a role in contributing to starch biosynthesis [122,123]. Rice pho1 mutant shows an accumulation of smaller starch granules and abnormal endosperm phenotype [124], and the amylopectin showed a higher proportion of short chains of DP < 11 and a lower proportion of intermediate chains of DP 13-21.…”
Section: Additional Enzymes (Disproportionating Enzyme and Starch Phomentioning
confidence: 99%